EVALUASI PEMBOROSAN MESIN JUMBO LOOM BERBASIS PENDEKATAN STATISTICAL PROCESS CONTROL - Nofanda, Taraz Atillah; Mahbubah, Nina Aini (Fakultas Teknik, Universitas Riau Kepulauan, 2023)
Continuous quality control along the production line is a crucial factor in achieving high productivity. PT. TRZ is a producer of various types of plastic-based products that implement strict quality control standards. However, it is still found that production targets still need to be achieved due to machine damage. This machine breaks. The company needs to be able to fulfill consumer orders on time. This research aims to evaluate product defects resulting from damage to the Jumbo Loom machine. Statistical process control evaluates factors in cutting machine defects, thread splice marks, and sheet shrinkage. The research results show that the company faces problems regarding machine defects, including machine running, thread splice marks, and shriveled sheets. This research aims to reduce defects in machines. The Seven Tools method is used to make repairs. From the processing results on the control chart, there were daily defects that exceeded the control limits. Therefore, it was carried out using a fishbone diagram. The processing results obtained 23 indicators of the causes of the three types of defects.